2003
DOI: 10.1093/hmg/ddg218
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal association of mutant huntingtin with synaptic vesicles inhibits glutamate release

Abstract: In Huntington disease (HD), polyglutamine expansion causes the disease protein huntingtin to aggregate and accumulate in the nucleus and cytoplasm. The cytoplasmic huntingtin aggregates are found in axonal terminals and electrophysiological studies show that mutant huntingtin affects synaptic neurotransmission. However, the biochemical basis for huntingtin-mediated synaptic dysfunction is unclear. Using electron microscopy on sections of HD mouse brains, we found that axonal terminals containing huntingtin agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 54 publications
1
61
0
Order By: Relevance
“…Huntingtin associates with microtubules and various vesicles including mitochondria and synaptic vesicles (DiFiglia et al, 1995;Bhide et al, 1996;Velier et al, 1998;Li et al, 2003). Both huntingtin and the huntingtin-associated protein 1 (HAP1) move in axons in both anterograde and retrograde directions (Block-Galarza et al, 1997) and have been reported to associate with both the anterograde and retrograde transport machinery (Engelender et al, 1997;Li et al, 1998;McGuire et al, 2006;Caviston et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Huntingtin associates with microtubules and various vesicles including mitochondria and synaptic vesicles (DiFiglia et al, 1995;Bhide et al, 1996;Velier et al, 1998;Li et al, 2003). Both huntingtin and the huntingtin-associated protein 1 (HAP1) move in axons in both anterograde and retrograde directions (Block-Galarza et al, 1997) and have been reported to associate with both the anterograde and retrograde transport machinery (Engelender et al, 1997;Li et al, 1998;McGuire et al, 2006;Caviston et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when huntingtin contains the polyQ expansion, its ability to transport BDNF-containing vesicles and to promote neuronal survival is lost . Finally, aggregates are also found in neurites and could also participate in neuronal dysfunction by altering the microtubule network dynamics and/or axonal transport (Li et al, 2000(Li et al, , 2003Gunawardena et al, 2003;Szebenyi et al, 2003;Guzik and Goldstein, 2004;Lee et al, 2004;Trushina et al, 2004;Charrin et al, 2005). Several posttranslational modifications such as proteolysis, ubiquitination, and sumoylation modify the toxicity of huntingtin (Kalchman et ).…”
Section: Introductionmentioning
confidence: 99%
“…Li demonstrated that mutant htt may interact with synaptic vesicle membrane proteins or proteins associated with vesicles in axonal terminals. One of these interacting proteins may be Huntingtin-associated protein1 (HAP1) 3,11,20 . Steroid hormone receptors are a special type of receptors because of their localisation in the cytoplasm or nucleus of eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that HD presents with a varied clinical picture prompted us to study the pathways and functions of steroid hormone receptors in vitro and mainly on HD model in animal. As we know, HD mouse model was compiled and as stipulated by Li 11 , we know that studies comprising HD mouse models provide compelling evidence to the fact that the N-terminal fragments of mutant Huntingtin protein(htt) with expanded glutamine repeat (82Q or 150Q) "cause neurological symptoms resembling some of the clinical features of HD" 2,11,14 . By constructing plasmid pEGFP-C2-ERα and others we would like to utilise the potential cooperation of SHR on HD for the purposes of highlighting the potential and prospective methods of assisting in remedying the behavioural, cognitive and memory defi ciencies found in HD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation